Transforming it operations management through applied engineering practices: a framework for success - Lolin, Vadym (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
This paper examines the effect of applied engineering practices on operational efficiency of IT management in a very competitive and technology driven environment. A panel data of 8 companies in different industries from 2019 to 2023 is analyzed to investigate the relationship between engineering practices (Lean IT and DevOps) and key performance indicators (system uptime, incident resolution time, and cost efficiency). The author demonstrates that organizations who have adopted these engineering practices have realized substantial improvements in operational performance. Continuous improvement and agile methodologies, when coached into companies, lead to longer term sustainability in terms of cost efficiency and scalability. In addition, the research illustrates the importance of organizational factors like resource allocation, employee training, and autonomy of decisions in improving the performance of these engineering practices. The results also highlight the need for combining applied engineering practices with strong managerial leadership and a reliance on data driven decision making to succeed in competitive global markets. Besides, the research illustrates how engineering practices, including the incorporation of these automation and AI technologies, act as a strategic enabler to decrease operational complexity and accelerate innovation.